Prenatal Diagnosis of Sirenomelia - Özek, Aykut; Turğal, Mert; Özyüncü, Özgür; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2013)
Sirenomelia is a rare and lethal congenital malformation. It is associated with a variety of anomalies and oligo/anhydramniosis. We present a case of sirenomelia detected in early second trimester presenting with anhydramniosis.